Not the skier - but the slope turns the skis - Kassat, G. (Science and Skiing IV, 2009)
INTRODUCTION: During the 15t International Congress on Science and Skiing, l gave the lecture "Turning the Skis without Mechanisms of Turning;" however, when performing parallel turns, there is evidently a rotary motion of the skis. This implies the question: "Who turns the skis?" In the first instance, the answer (cf. the title) is not plausible and has to be explained.